PCR-RFLP genotyping of C1q mutations and single nucleotide polymorphisms in Malaysian patients with systemic lupus erythematosus - Chew, C.H.; Chua, K.H.; Lian, L.H.; Puah, S.M.; Tan, S.Y. (2008)
Five types of known mutations within the C1q gene located at C1qA-Gln186 (C > T), C1qB-Gly15 (G > A), C1qB-Arg150 (C > T), C1qC-Gly6 (G > A), and C1qC-Arg41 (C > T) and two SNPs located at C1qA-Gly70 (G/A) and C1qC-Pro14 (T/C) were screened in a multiracial Malaysian population. One hundred thirty patients with systemic lupus erythematosus (SLE) and 130 matched healthy control subjects were genotyped using PCRRFLP methods. We found no occurrence of the five types of mutations in either the homozygous or heterozygous form among the 260 samples studied. Statistical analysis also revealed that there were no significant associations observed in the genotype distributions and allele frequencies among the patients with SLE and healthy control subjects with both C1qA-Gly70 (G/A) and C1qC-Pro14 (T/C) SNPs. Overall, C1q deficiency was not proven as a primary causative genetic predisposition factor for SLE in the Malaysian population.